Using Progressive Muscle Relaxation for Reducing Fatigue among Truck Drivers - Deasy Siregar, Santy; Judea Samosir, Frans; Isabella Silalahi , Marlinang; Aditya Kurnia , Muhammad; Manalu , Putranto; Sweeta Silaban , Ray; Sabarina Tarigan , Rimma (Journal of Health Education, 2024)
Background: Long working hours, poor working conditions, and irregular sleep patterns increase the risk of burnout in freight truck drivers. Progressive muscle relaxation (PMR) is a procedure to relax muscles. This study aims to analyze the effectiveness of progressive muscle relaxation on truck drivers. Methods: This research is a quasi-experimental study with one group pretest-posttest design. 60 truck drivers working in Belawan Port were given PMR video tutorials and underwent PMR therapy for two months. The researcher used the standard KAUPKK questionnaire to measure subject fatigue. The data were tested using the Wilcoxon Signed-Rank test. Results: With a z score (-5.798) greater than the z-table value (-1.645) and a p-value of 0.000, it can be concluded that there are differences in complaints of fatigue among truck drivers before and after PMR. Conclusions: The results of this study indicate that the fatigue of truck drivers can be reduced by PMR therapy.